Metropolização e mobilidade: análise dos deslocamentos intrameptropolitanos de estudantes na região metropolitana de Goiânia, 2010 a 2013 - Alencar, Diego Pinheiro (2014)
The present research untitled, “Metropolization and mobility: analysis of intra-metropolitan commuting of students in Goiânia’s Metropolitan Region, 2010 to 2013” aims to analyze how the mass transit provides the integration of common public interest functions in Goiânia’s Metropolitan Region (RMG). Therefore, the study verticalizes in middle and high levels of schools in the state of Goiás. In the first chapter, the process of metropolization becomes the central element to be analyzed. By the bibliography common aspects are presented in 19 th century European metropolises with the Brazilian metropolitan environments. The secondary data permit the analysis of social and spatial dynamics present in different Brazilian metropolitan environments. In the second chapter, the spatial mobility is questioned as an important process for the comprehension of the intra-metropolitan dynamics of RMs. Mass transit is the main focus of action of managers in metropolitan spaces. Nevertheless, the barriers are present in the installment of the service, which reaches directly in others aspects of mobility, as the growth of the private vehicles. The organization of the following service is fundamental for the effectiveness in the intra-municipal commutings. In the third chapter occurs the spatialization and analyzis of the intra-municipal commutings of students. Therefore, is necessary the intra-urban reading of Goiânia related to the intra-metropolitan configuration of the RMG. The concept of centralization contributes effectively for the dynamics comprehension, since the major flows orientation of students have as destiny the macrozones of Centro and Campinas. Ultimately, the research aims to present how the organization of urban/metropolitan forms organizes the social relations in the RMG.